Jan Massys (c. 1510-1573) Renaissance painter of Flemish female beauty - Galassi, Maria Clelia 1954- (Brepols, 2023)
"The painter Jan Massys (c. 1510-1573) trained under his father Quinten, succeeding him after his death (1530) at the head of Antwerp's most famous workshop. However, his career, destined for certain success, was abruptly cut short in 1544. Condemned for joining the Loysts sect, he had to flee Antwerp, finding refuge perhaps initially in France and at one point in Italy. Only in 1555 was he able to return to his homeland, regaining his artistic leadership within a few years. His oeuvre consists exclusively of works for private use and is characterized, in particular, by the depiction of elegant and seductive nude or half-naked female figures, protagonists of biblical or mythological subjects. The identification of the patron of the 1561 Venus with the view of Genoa (Stockholm, Nationalmuseum) in the person of the noble Genoese banker Ambrogio di Negro, offered the possibility of reconstructing the social context of the artist's clientele and his relations with those intellectuals – both Genoese and Flemish-who gave life to the lively humanist academies of Antwerp. The figure emerges of a cultivated and particularly refined painter, who shared with his patrons the ideals of neo-Petrarchan poetry and executed paintings of great preciousness, characterized by a meticulous and skillful painting technique."
Rückentitel: "Jan Massys"
Die Bandangabe wurde auf der Internetseite des Verlags ermittelt
Literaturverzeichnis: Seite 223-231
Keywords: Massys, Jan -- 1509-1575; Frau -- Motiv; Malerei